Finite element analysis of braced excavation in sand - Lee, Si Min (Nanyang Technological University, 2022)
Through human ingenuity, land-scarce Singapore has found innovative ways to overcome her natural constraints by going underground. Currently, Singapore’s underground houses pedestrian underpasses, expressways, an underground transport system, electrical substations and storage facilities. The development of underground facilities has necessitated braced excavations to provide access for manpower and equipments into the ground underneath to carry out these construction projects.